2007
DOI: 10.1002/ps.1451
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residues in beeswax samples collected from honey bee colonies (Apis mellifera L.) in France

Abstract: In 2002 a field survey was initiated in French apiaries in order to monitor the health of honey bee colonies (Apis mellifera L.). Studied apiaries were evenly distributed across five sites located in continental France. Beeswax samples were collected once a year over 2 years from a total of 125 honey bee colonies. Multiresidue analyses were performed on these samples in order to identify residues of 16 insecticides and acaricides and two fungicides. Residues of 14 of the searched-for compounds were found in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 22 publications
2
123
0
Order By: Relevance
“…Not only acaricide contamination occurs, residues of the OC lindane, and the OCs metabolites p,p'-TDE, endosulfan sulphate and 3-phenoxybenzaldehide were found in beeswax from Spanish beehives (Jiménez et al, 2005). A wide variety of residues of OPs, synthetic pyrethroids and dicarboximide fungicides (procymidone and vinclozolin) were also detected in beeswax from France (Chauzat & Faucon 2007). Recently, Spanish commercial beeswax were found containing chlorimefon, chlorfenvinphos, chlorpyriphos, endosulfan and malathion residues (Serra-Bonvehí & Orantes-Bermejo, 2010).…”
Section: Pesticide Residues In Bee's By-products: Propolis and Beeswaxmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only acaricide contamination occurs, residues of the OC lindane, and the OCs metabolites p,p'-TDE, endosulfan sulphate and 3-phenoxybenzaldehide were found in beeswax from Spanish beehives (Jiménez et al, 2005). A wide variety of residues of OPs, synthetic pyrethroids and dicarboximide fungicides (procymidone and vinclozolin) were also detected in beeswax from France (Chauzat & Faucon 2007). Recently, Spanish commercial beeswax were found containing chlorimefon, chlorfenvinphos, chlorpyriphos, endosulfan and malathion residues (Serra-Bonvehí & Orantes-Bermejo, 2010).…”
Section: Pesticide Residues In Bee's By-products: Propolis and Beeswaxmentioning
confidence: 99%
“…In this case, the preferred strategy is based on the retention of waxes in the sorbent whereas pesticides are eluted. Methodologies using Florisil (Adamczyk et al, 2007, Frison et al, 1999, Tsigouri et al, 2000, Tsigouri et al, 2004, C 18 (Chauzat & Faucon, 2007, Jiménez et al, 2004a, Kamel & Al-Ghamdi, 2006) also combined with HLB (Jiménez et al 2004b) were reported. Selective eluting step is carried out using non-polar mixtures (nhexane:diethylether mixtures) to polar ones (based on MeOH and MeCN), respectively.…”
Section: Solid Phase Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high levels of agrochemical and miticide residues, including neonicotinoids, have been measured in pollen loads, bee bread, honey and propolis, as well as in the wax cells in which larvae develop and pollen is stored (Chauzat and Faucon, 2007;Chauzat et al, 2006;Mullin et al, 2010;Pettis et al, 2013;Wu et al, 2011). Wax may be a sink for hydrophobic chemicals (Chauzat and Faucon, 2007), which facilitates the transfer of pesticides from contaminated to uncontaminated comb (Wu et al, 2011). Larvae, far from being protected from pesticides in the colony, may thus be chronically exposed to an accumulation of chemical residues with potential additive or synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the active ingredient is commonly found in the hive and in pollen pellets of foragers (Chauzat et al, 2006;Chauzat and Faucon, 2007).…”
Section: Thiaclopridmentioning
confidence: 99%